PERSEPSI MAHASISWA TERHADAP KUALITAS PELAYANAN PENDIDIKAN FIP IKIP PGRI MADIUN - Hartini, Hartini; Gunawan, Imam; Nurina Suraya, Selly (Jurnal Pendidikan, 2012)
Education service quality very irrespective influence that given from a service user expectation with that perception by service user. One of the factor that determine customer satisfaction service quality that consist of five service dimensions: reliability, responsiveness, assurance, empathy, and tangible. Education service quality baseds on from human resource that is lecturer, staff, and facilities. This research aim detects student university perception towards education service quality FIP IKIP PGRI MADIUN. This research uses to approach quantitative as a mean to analyze difference between perception and expectation student university towards education service. This research is done to describe service quality and student university satisfaction level. Research respondent as much as 293 student niversities from total 1099 student universities. Sample taking uses technique proportional random sampling. Research data is got by using closed model inquiry instrument. Data analysis technique that used: descriptive analysis; analysis of variance; and analysis performance and importance matrix. Research result shows that: (1) level expectation student university about education service quality belongs in category very high; (2) student university perception level about education service quality belongs in high category; and (3) there difference between expectation and student university perception about education service quality.Key words: Education Service Quality, Expectation, Perception